(untitled) (Journal of Economic Additions, 2025)
This research aims to analyze the dynamics of short-term interest rates using the Vasicek model (1977), one of the most widely used stochastic models for predicting interest rate movements. The model relies on a differential equation that describes the evolution of interest rates over time. By analyzing data on the U.S. federal funds rate (FEDFUNDS) over the period 1990-2025, the model parameters were estimated using the Ordinary Least Squares (OLS) method. The results indicate that the model provides a robust framework for analyzing interest rate behavior. Jel Classification Codes: C61; E51.